THE EFFECTIVENESS OF THE READ-ASK-PARAPHRASE (RAP) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Ali Baba; Ana Kuliahana (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2022)
The aim of this research was to improve students' reading comprehension at the X grade of SMA Negeri 1 Kasimbar. The method applied was the quasi-experimental design with no equivalent control group, the design involved two groups of class. One group was treated as the experimental class, and another class group was the control class. In the experimental class, the researcher applied The RAP strategy and for the control class, the researcher does not apply this strategy. The population of this research was the X grade of SMA Negeri 1 Kasimbar which consisted of 168 students. The sample of this research consisted of 20 students, with the selected date by using the purposive sampling technique, 10 students for X IPA 3 as experimental class and 10 students from X IPA 2 as control class. The instrument used in this research was a reading test. The test was used in the pre-test and post-test. The implementation of this research was to improve the reading comprehension of the students by the (RAP) strategy. The mean score on the reading test before treatment with the (RAP) strategy read ask paraphrase was 60 and after treatment, the mean score was improved by 79.5. It means that the read-ask paraphrase (RAP) strategy to improve students' reading comprehension at the X grade of SMA Negeri 1 Kasimbar is effective.